The implementation of 5s for improving organization in UiTM furniture workshop / Imran Mustapa - Mustapa, Imran (2012)
The purpose of this study was to observe the way of implementing the 5S methodology in the furniture workshop in UiTM Pahang. In the framework of this research it has been analyzed and implemented the 5S rules in the production process. On the basis of the own research it can be stated that, introducing the 5S rules bring great changes in the workshop, for example: process improvement, maintenance and improvement of the machines' efficiency, and increased safety. The 5S methodology analyzes the processes running on the workplace. The 5S is the methodology of creating and maintaining well- organized, clean, highly effective and high quality workplace. The results clearly showed that training all staff and students on the 5S rules. The essential thing is to divide activities into some 5S main steps and to maintain continuous improvement. It results in effective organization in UiTM Pahang furniture workshop.